Integrated assessment of surface water quality and seasonal variability using CCME-WQI in a high-Andean watershed of southern Peru - Arteaga, Ruby Juniors Alvarez; Berrios, Wilson Calsin; Charaja, William Santiago Palacios; Roque, Maribel Mamani; Ramirez, Alexander Aguilar; Ramirez, Johan Denis Aguilar (Journal of Degraded and Mining Lands Management, 2026)
It is essential to sustain water quality to support environmental sustainability and public health, particularly in high-Andean watersheds, which are sensitive to hydrological variability. The present study is an integrated assessment of surface water quality conducted in the Ilave District of southern Peru, using the Canadian Council of Ministers of the Environment Water Quality Index (CCME-WQI). Surface water quality was assessed based on the evaluation of physicochemical parameters, microbiological indicators, and concentrations of selected trace metals during contrasting dry and wet seasonal conditions and the application of the components of the CCME-WQI to assess the quality of the overall surface water. Results from this study indicate significant spatial and temporal variability in surface water quality; however, most monitoring locations were classified as having good to excellent water quality. Lower CCME-WQI index values were primarily attributed to localized microbiological contamination and higher concentrations of selected trace metals during low-flow conditions. In general, the CCME-WQI successfully integrated multi-parameter surface water quality data and identified localized degradation processes; therefore, there is a need for targeted monitoring and science-based management of water resources in areas that are subject to increasing anthropogenic pressures in high-Andean environments.